Composite copper foil and preparation method thereof

By performing corona treatment and hole punching on the PP base film, combined with the coating and electroplating of conductive paste and copper film layer, the problems of defects and insufficient conductivity after the thickness of the composite copper foil are reduced, and the composite copper foil is realized Good adhesion and excellent conductivity, suitable for a variety of battery types.

CN119433633AInactive Publication Date: 2025-02-14DONGGUAN WANFENG NANOMETER MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411600407.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing composite copper foil is prone to defects after the thickness decreases, such as pinholes, wrinkles, and depressions, resulting in uneven surface coating, increasing the internal resistance of the battery, reducing cycle life, and at the same time, the mechanical strength decreases, which easily breaks, affecting the stability of the negative electrode. Sex and flatness.

Method used

The PP base film is pretreated by corona treatment and hole punching technology to form a porous structure, and then the conductive paste and electroplated copper film layer are coated on its surface to fill through holes to improve adhesion and electrical conductivity.

Benefits of technology

Through the improved preparation method, the PP base film of the composite copper foil has good adhesion and excellent conductivity, which solves the problem of difficulty in electrolyte injection in battery preparation and is suitable for secondary batteries and semi-solid state Batteries and solid-state batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a composite copper foil and a preparation method thereof, and the preparation method of the composite copper foil comprises the following steps: (1) carrying out corona treatment on the upper and lower surfaces of a PP base film to obtain a surface-treated PP base film; (2) punching along the direction perpendicular to the upper and lower surfaces of the surface-treated PP base membrane to form a plurality of through holes, so as to obtain a porous PP base membrane; (3) the upper surface and the lower surface of the porous PP base film are coated with conductive slurry, conductive film layers are formed, and the conductive slurry comprises acrylic resin and a conductive agent; and (4) electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer and fill the through hole at the same time. Good adhesive force exists between the PP base film and the film layers (the conductive film layer and the copper film layer) in the composite copper foil, and the composite copper foil has excellent conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a composite copper foil and a preparation method thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry in recent years, the strong demand for power lithium batteries has driven the rapid development of the copper foil industry. Copper foil has been widely used as a negative electrode current collector for lithium batteries. As a current carrier, the main function of lithium battery copper foil is to collect the small current generated by the negative electrode active material into a large current output. Due to its relatively single function, in order to effectively improve the battery energy storage performance, lithium battery copper foil continues to develop in the direction of lightness, thinness and toughness. Due to the reduction in thickness, copper foil is prone to defects such as pinholes, wrinkles, and depressions during production, resulting in uneven coating thickness when the active material is applied to its surface, and even leakage points or penetration, which increases the internal resistance of the battery and reduces the cycle life. At the same time, the thickness is reduced, and its mechanical strength is greatly reduced, which makes it easy to break during the negative electrode production process, affecting the stability and flatness of the negative electrode size. At present, the composite copper foil prepared by sputtering using organic film as a carrier has both the excellent plasticity of polymers and can reduce the overall weight of copper foil, greatly reducing the amount of copper raw materials. At the same time, the insulating organic thin film intermediate carrier is beneficial to improving the safety of the battery and is a new type of lithium battery negative electrode current collector material with great potential in the current lithium battery industry.

[0003] The typical composite copper foil is a sandwich structure. The middle layer is other materials used to replace metallic copper. A thin copper layer is plated on both sides of the material to make its surface have the characteristics of metallic copper. At present, the most commonly used composite copper foil middle layer material is polymer film. This type of polymer film material has a significant price advantage over metallic copper. As a negative electrode current collector, it will also give lithium batteries lightweight characteristics to a certain extent. Commonly used polymer films include polyethylene terephthalate (PET) base film, polyimide (PI) base film, polypropylene (PP) base film, etc. Among them, PET film has low cost, but is not resistant to corrosion by lithium hexafluorophosphate electrolyte. After a certain number of cycles, the PET film dissolves, resulting in a significant decrease in battery performance; PI base film has good mechanical properties, and after surface treatment, it can show strong hydrophilicity and has strong bonding with the surface copper layer, but its price is too high. If it is selected as the intermediate support layer material, it has no advantage over the existing pure copper foil in terms of raw material cost. The PP base film does not contain ester bonds, is resistant to corrosion by acidic substances such as lithium hexafluorophosphate electrolyte, and has a low cost. However, since PP materials are mainly carbon-hydrogen bonds, carbon-hydrogen bonds in organic compounds are generally considered to be non-polar covalent bonds. As a result, the PP material has a lower polarity, a looser molecular chain structure, and a low crystallinity. The interface energy between PP and copper foil is higher, the intermolecular interaction is weak, and the adhesion is very low. During the battery cycle test, the material continues to expand and contract, and the interface between the PP material base film and copper will peel off. The PP film has poor adhesion to the copper layer.

[0004] Therefore, there is an urgent need for a composite copper foil and a preparation method thereof to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a composite copper foil and a preparation method thereof. The composite copper foil of the present invention has good adhesion between the PP base film and the film layer (conductive film layer, copper film layer) and has excellent conductive properties.

[0006] To achieve the above object, the present invention provides a method for preparing a composite copper foil, comprising:

[0007] (1) performing corona treatment on the upper and lower surfaces of the PP base film to obtain a surface-treated PP base film;

[0008] (2) punching holes in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes to obtain a porous PP base film;

[0009] (3) coating a conductive paste on the upper and lower surfaces of the porous PP base film to form a conductive film layer, wherein the conductive paste comprises an acrylic resin and a conductive agent;

[0010] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer and simultaneously fill the through hole.

[0011] Compared with the prior art, the present invention firstly performs corona treatment on the PP base film and then perforates it, and then applies a conductive paste on the upper and lower surfaces of the porous PP base film, wherein the conductive paste includes an acrylic resin and a conductive agent. The surface tension of the PP base film after the corona treatment is large, and groups with strong polarity such as carbonyl and peroxide are generated, thereby significantly improving the adhesion of the acrylic resin to the surface of the PP base film. The coating process can further make the conductive paste evenly adhere to the upper and lower surfaces of the PP base film, thereby improving the conductive performance of the conductive film layer. At the same time, the porous PP base film has a number of through holes, and a copper film layer can be filled in the through holes during copper electroplating to form a copper film layer. The copper film layer in the through hole connects the copper film layer located on the upper and lower surfaces of the PP base film, further improving the connection between the copper film layer and the PP base film, and at the same time, the copper film layers located on the upper and lower surfaces of the PP base film can transmit current to each other, further improving the conductive effect of the composite copper foil of the present invention. Therefore, the composite copper foil of the present invention has good adhesion between the PP base film and the film layer (conductive film layer and copper film layer), and has excellent conductive performance.

[0012] Furthermore, the acrylic resin of the present invention is a solvent-based acrylic resin with a solid content of 10 to 30%.

[0013] Furthermore, the conductive agent of the present invention is selected from at least one of graphite, graphene, carbon nanotubes, nanosilver wires and metal particles, and the mass percentage of the conductive agent in the conductive paste is 3-10%.

[0014] Furthermore, the sheet resistance of the conductive film layer of the present invention is 0.5-20Ω.

[0015] Furthermore, the treatment voltage of the corona treatment of the present invention is 3.0KV-5.0KV, the current is 8A, the corona speed is 8-10m / s, and the treatment time is 12-15s.

[0016] Furthermore, the diameter of the through hole of the present invention is 0.2-0.5 μm, and the distance between two adjacent through holes is 2-5 mm.

[0017] Furthermore, the thickness of the PP base film of the present invention is 2 to 100 μm.

[0018] Furthermore, the thickness of the conductive film layer of the present invention is 0.5-5 μm.

[0019] Furthermore, the copper film layer of the present invention has a thickness of 0.5 to 2 μm.

[0020] Furthermore, the plating solution used for electroplating copper of the present invention comprises 80-150 g / L of copper sulfate, 50-120 g / L of sulfuric acid and 0.01-2 g / L of additives, the copper plating temperature is 20-35° C., the copper plating current density is 2-10 ASD, and the copper plating time is 1-20 min.

[0021] Another aspect of the present invention provides a composite copper foil, which is prepared by the above-mentioned preparation method. The composite copper foil of the present invention has good adhesion between the PP base film and the film layer (conductive film layer, copper film layer), and has excellent conductivity, and is suitable for secondary batteries. And because the composite copper foil of the present invention has a plurality of through-hole structures, it helps to solve the problem of difficulty in injecting electrolytes in battery preparation, so it is particularly suitable for semi-solid batteries and solid-state batteries. DETAILED DESCRIPTION

[0022] The present invention discloses a method for preparing a composite copper foil, comprising:

[0023] (1) performing corona treatment on the upper and lower surfaces of the PP base film to obtain a surface-treated PP base film;

[0024] (2) punching holes in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes, thereby obtaining a porous PP base film;

[0025] (3) coating a conductive paste on the upper and lower surfaces of the porous PP base film to form a conductive film layer, wherein the conductive paste includes an acrylic resin and a conductive agent;

[0026] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer and fill the through holes at the same time.

[0027] In (1), the PP base film is subjected to corona treatment. After the corona treatment, the molecular chains of the surface layer of the PP base film are broken and the molecular weight is reduced, and carbonyl groups, peroxide groups and other highly polar groups are formed on the surface, thereby increasing the surface tension of the PP base film and facilitating the subsequent loading of the conductive film layer. Specifically, the thickness of the PP base film can be 2 to 100 μm, about 5 to 90 μm, about 8 to 80 μm or about 10 to 50 μm. As an example, the thickness of the PP base film may be, but is not limited to, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, or 100μm.

[0028] Corona treatment is a conventional technique in the art, and the specific operation is not limited here, and the operation can be performed according to the conventional method in the art. As for the working conditions of the corona treatment, as an example, the treatment voltage can be 3.0KV to 5.0KV, the current can be 8A, the corona speed can be 8 to 10m / s, and the treatment time can be 12 to 15s. Specifically, the processing voltage may be, but is not limited to, 3.0KV, 3.2KV, 3.4KV, 3.6KV, 3.8KV, 1.0KV, 4.2KV, 4.4KV, 4.6KV, 4.8KV, 5.0KV; the corona speed may be, but is not limited to, 8.0m / s, 8.2m / s, 8.4m / s, 8.6m / s, 8.8m / s, 9.0m / s, 9.2m / s, 9.4m / s, 9.6m / s, 9.8m / s, 10m / s; the processing time may be, but is not limited to, 12s, 12.5s, 13s, 13.5s, 14s, 14.5s, 15s;

[0029] In (2), the surface-treated PP base film is punched to obtain a porous PP base film. The punching can be performed by laser punching, mechanical punching or ultrasonic punching. In some preferred embodiments, the punching is performed by laser punching. Laser punching, mechanical punching and ultrasonic punching are all conventional punching techniques in the art. The specific operations are not limited in the present invention, and the conventional processes in the art can be used. The through holes of the present invention can be arranged in an array or in an irregular arrangement. For the array arrangement, it is preferably arranged in an array and staggered. The aperture of the through hole is 0.2 to 0.5 μm. As an example, the aperture of the through hole can be, but not limited to, 0.2 μm, 0.3 μm, 0.4 μm, and 0.5 μm. The distance between two adjacent through holes is 2 to 5 mm. For example, the distance between two adjacent through holes may be, but is not limited to, 2.0 mm, 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.8 mm, 4.0 mm, 4.2 mm, 4.4 mm, 4.6 mm, 4.8 mm, or 5.0 mm.

[0030] In (3), a conductive paste is applied to the upper and lower surfaces of the porous PP base film and dried to form a conductive film layer. The conductive paste includes an acrylic resin and a conductive agent. The acrylic resin is a solvent-based acrylic resin with a solid content of 10 to 30%. For example, the solid content of the solvent-based acrylic resin may be, but is not limited to, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%. The solvent may specifically be toluene, xylene, acetone, an alcohol solvent, and an ester solvent. Specifically, the alcohol solvent may be, but is not limited to, at least one of methanol, ethanol, propanol, ethylene glycol, and propylene glycol; the ester solvent may be, but is not limited to, at least one of ethyl acetate, butyl acetate, and diethyl carbonate.

[0031] The conductive agent is selected from at least one of graphite, graphene, carbon nanotubes, nanosilver wires and metal particles, wherein the metal particles are specifically flaky metal particles with a D50 of less than 1 μm. The mass percentage of the conductive agent in the conductive paste is 3 to 10%. As an example, the mass percentage of the conductive agent in the conductive paste may be, but is not limited to, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. The square resistance of the conductive film layer is 0.5-20Ω. For example, the square resistance of the conductive film layer may be, but is not limited to, 0.5Ω, 1.0Ω, 1.5Ω, 2.0Ω, 2.5Ω, 3.0Ω, 3.5Ω, 4.0Ω, 4.5Ω, 5.0Ω, 5.5Ω, 6.0Ω, 6.5Ω, 7.0Ω, 7.5Ω, 8.0Ω, 8.5Ω, 9.0Ω, 9.5Ω, 10.0Ω, 11Ω, 12Ω, 13Ω, 14Ω, 15Ω, 16Ω, 17Ω, 18Ω, 19Ω, and 20Ω. The larger the square resistance, the worse the conductive performance.

[0032] The thickness of the conductive film layer may be, but is not limited to, 0.5 to 5 μm. For example, the thickness of the conductive film layer may be, but is not limited to, 0.5 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.4 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.6 μm, 4.8 μm, 5.0 μm. Drying may be performed in an oven at a temperature of 80 to 120° C. For example, the drying temperature may be, but is not limited to, 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., 120° C.

[0033] In (4), a copper film layer is formed on the upper and lower surfaces of the conductive film layer by an electroplating process. The copper film layer formed by electroplating can also be filled in the through hole. The copper film layer in the through hole is connected with the copper film layers on the upper and lower surfaces to form a sandwich structure, which further improves the adhesion between the copper film layer and the PP base film and avoids the copper film layer from falling off to a large extent. The copper electroplating process is a conventional technology in the art. In some embodiments, the plating solution used for copper electroplating includes 80-150 g / L of copper sulfate, 50-120 g / L of sulfuric acid and 0.01-2 g / L of additives. By way of example, the concentration of copper sulfate may be, but is not limited to, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, and 150 g / L; the concentration of sulfuric acid may be, but is not limited to, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 105 g / L, 110 g / L, 115 g / L, and 120 g / L. The additives may be brighteners, levelers, etc. Specifically, the brightener may be sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, sodium N,N-dimethyl-dithiocarbonyl propane sulfonate, etc. The leveler may be polyethylene glycol, etc. The copper plating temperature is 20 to 35°C, the copper plating current density is 2 to 10 ASD, and the copper plating time is 1 to 20 minutes. As an example, the temperature of copper plating may be but is not limited to 20°C, 21°C, 22°C, 24°C, 25°C, 26°C, 28°C, 30°C, 32°C, 33°C, 34°C, 35°C; the current density of copper plating may be but is not limited to 2ASD, 3ASD, 4ASD, 5ASD, 6ASD, 7ASD, 8ASD, 9ASD, 10ASD; the time of copper plating may be but is not limited to 1min, 2min, 3min, 4min, 5min, 6min, 8min, 10min, 12min, 14min, 16min, 18min, 20min. The thickness of the copper film layer is 0.5-2 μm. For example, the thickness of the copper film layer may be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, and 2.0 μm. After the copper film layer is formed by electroplating copper, it is washed and dried.

[0034] Another aspect of the present invention provides a composite copper foil, which is prepared by the above-mentioned preparation method. The composite copper foil of the present invention has good adhesion between the PP base film and the film layer (conductive film layer, copper film layer), and has excellent conductive properties. And because the composite copper foil of the present invention has a plurality of through-hole structures, it helps to solve the problem of difficulty in injecting electrolytes in battery preparation, and is suitable for secondary batteries, and is particularly suitable for semi-solid batteries and solid-state batteries.

[0035] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0036] Example 1

[0037] This embodiment provides a method for preparing a composite copper foil, comprising:

[0038] (1) performing corona treatment on the upper and lower surfaces of a PP base film having a thickness of 10 μm to obtain a surface-treated PP base film. The corona treatment voltage is 3.2 KV, the current is 8 A, the corona speed is 8.5 m / s, and the treatment time is 12 s;

[0039] (2) performing laser drilling in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes, thereby obtaining a porous PP base film. The through holes are arranged in an array and staggered, the aperture of the through holes is 0.2 μm, and the distance between two adjacent through holes is 2.5 mm;

[0040] (3) Applying conductive paste on the upper and lower surfaces of the porous PP base film and drying at 85°C to form a conductive film layer with a thickness of 0.6 μm. The conductive paste includes 86% toluene solution, 10% acrylic resin with a solid content and 4% graphite, and the square resistance of the conductive film layer is 0.8Ω;

[0041] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer with a thickness of 0.5 μm. The electroplating solution includes an aqueous solution of 85 g / L copper sulfate, 60 g / L sulfuric acid, 0.01 g / L sodium 3-mercapto-1-propyl sulfonate, 0.01 g / L sodium polydisulfide dipropane sulfonate and 0.02 g / L polyethylene glycol, and electroplating is performed at 22° C. with a current density of 6 ASD for 2 minutes to form a copper film layer and fill the through holes at the same time, and finally washed with water and dried.

[0042] Example 2

[0043] This embodiment provides a method for preparing a composite copper foil, comprising:

[0044] (1) performing corona treatment on the upper and lower surfaces of a PP base film having a thickness of 50 μm to obtain a surface-treated PP base film. The corona treatment voltage is 4.0 KV, the current is 8 A, the corona speed is 9.3 m / s, and the treatment time is 13 s;

[0045] (2) Laser drilling is performed in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes, thereby obtaining a porous PP base film. The through holes are arranged in an array and staggered, the aperture of the through holes is 0.34 μm, and the distance between two adjacent through holes is 3 mm;

[0046] (3) Coating a conductive paste on the upper and lower surfaces of the porous PP base film and drying at 100°C to form a conductive film layer with a thickness of 1.2 μm. The conductive paste includes 72% diethyl carbonate solution, 20% acrylic resin with a solid content and 8% nano silver wires, and the square resistance of the conductive film layer is 3Ω;

[0047] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer with a thickness of 1 μm. The electroplating solution is an aqueous solution of 118 g / L copper sulfate, 105 g / L sulfuric acid, 0.02 g / L sodium 3-mercapto-1-propyl sulfonate, 0.02 g / L sodium polydisulfide dipropane sulfonate and 0.02 g / L polyethylene glycol, and electroplating is performed at a current density of 8 ASD for 5 minutes to form a copper film layer and fill the through holes at the same time, and finally washed with water and dried.

[0048] Example 3

[0049] This embodiment provides a method for preparing a composite copper foil, comprising:

[0050] (1) performing corona treatment on the upper and lower surfaces of a PP base film having a thickness of 85 μm to obtain a surface-treated PP base film, wherein the corona treatment voltage is 4.9 KV, the current is 8 A, the corona speed is 10 m / s, and the treatment time is 15 s;

[0051] (2) Mechanically punching in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes, thereby obtaining a porous PP base film. The through holes are arranged in an array and staggered, the aperture of the through holes is 0.46 μm, and the distance between two adjacent through holes is 4.5 mm;

[0052] (3) Coating a conductive paste on the upper and lower surfaces of the porous PP base film and drying at 115° C. to form a conductive film layer with a thickness of 5 μm. The conductive paste includes 62% ethylene glycol solution, 28% acrylic resin with a solid content, and 10% silver particles with a D50 of 0.05 μm. The sheet resistance of the conductive film layer is 5Ω;

[0053] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer with a thickness of 2 μm, wherein the electroplating solution is an aqueous solution of 135 g / L copper sulfate, 120 g / L sulfuric acid, 0.05 g / L sodium 3-mercapto-1-propyl sulfonate, 0.03 g / L sodium N,N-dimethyl-dithiocarbonylpropane sulfonate and 0.05 g / L polyethylene glycol, and electroplating is performed at a current density of 10 ASD for 10 min to form a copper film layer and fill the through holes at the same time, and finally washed with water and dried.

[0054] Comparative Example 1

[0055] This comparative example provides a method for preparing a composite copper foil, comprising:

[0056] (1) performing corona treatment on the upper and lower surfaces of a PP base film having a thickness of 10 μm to obtain a surface-treated PP base film. The corona treatment voltage is 3.2 KV, the current is 8 A, the corona speed is 8.5 m / s, and the treatment time is 12 s;

[0057] (2) performing laser drilling in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes, thereby obtaining a porous PP base film. The through holes are arranged in an array and staggered, the aperture of the through holes is 0.2 μm, and the distance between two adjacent through holes is 2.5 mm;

[0058] (3) Applying conductive paste on the upper and lower surfaces of the porous PP base film and drying at 85°C to form a conductive film layer with a thickness of 0.6 μm. The conductive paste includes 86% toluene solution, 10% polyurethane resin with a solid content and 4% graphite, and the square resistance of the conductive film layer is 0.8Ω;

[0059] (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer with a thickness of 0.5 μm. The electroplating solution includes an aqueous solution of 85 g / L copper sulfate, 60 g / L sulfuric acid, 0.01 g / L sodium 3-mercapto-1-propyl sulfonate, 0.01 g / L sodium polydisulfide dipropane sulfonate and 0.02 g / L polyethylene glycol, and electroplating is performed at 22° C. with a current density of 6 ASD for 2 minutes to form a copper film layer and fill the through holes at the same time, and finally washed with water and dried.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a composite copper foil, comprising:

[0062] (1) performing corona treatment on the upper and lower surfaces of a PP base film having a thickness of 10 μm to obtain a surface-treated PP base film. The corona treatment voltage is 3.2 KV, the current is 8 A, the corona speed is 8.5 m / s, and the treatment time is 12 s;

[0063] (2) coating the upper and lower surfaces of the porous PP base film with a conductive paste and drying at 85°C to form a conductive film layer with a thickness of 0.6 μm. The conductive paste includes 86% toluene solution, 10% acrylic resin with a solid content and 4% graphite, and the square resistance of the conductive film layer is 0.8Ω;

[0064] (3) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer with a thickness of 0.5 μm. The electroplating solution includes an aqueous solution of 85 g / L copper sulfate, 60 g / L sulfuric acid, 0.01 g / L sodium 3-mercapto-1-propyl sulfonate, 0.01 g / L sodium polydisulfide dipropane sulfonate and 0.02 g / L polyethylene glycol, and electroplating is performed at 22° C. with a current density of 6 ASD for 2 minutes to form a copper film layer and fill the through holes at the same time, and finally washed with water and dried.

[0065] The composite copper foils prepared by the preparation methods of Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to conductivity tests and adhesion tests according to the following test conditions, wherein adhesion refers to the adhesion between the film layer (conductive film layer, copper film layer) and the PP base film. The test results are shown in Table 1.

[0066] Conductivity test: Referring to "JIS H0505-1975 Resistivity and conductivity measurement methods of nonferrous metal materials", the conductivity (% IACS) at 25°C was measured by the 4-terminal method;

[0067] Adhesion test: Use a grid knife to cut through the film layer, then stick 3M tape on the grid test area, press it flat with your fingers to ensure there are no bubbles, and pull it quickly and forcefully after the tape and product form about 90 degrees. Test 3 times to check the integrity of the film layer in the grid area. The adhesion grade judgment standards are as follows: 5B if there is no film shedding, 4B if the film shedding area is less than 5%, 3B if the film shedding area is 5% to 15%, 2B if the film shedding area is 15% to 35%, 1B if the film shedding area is 35% to 65%, and 0B if the film shedding area exceeds 65%.

[0068] Table 1 Performance test results of the composite copper foil prepared in Examples 1 to 3 and Comparative Examples 1 to 2

[0069] Group Adhesion Electrical conductivity (%IACS) Example 1 5B 115 Example 2 5B 120 Example 3 5B 119 Comparative Example 1 4B 85 Comparative Example 2 3B 76

[0070] Specifically, as shown in the test results of Table 1, by comparing Examples 1 to 3 with Comparative Examples 1 to 2, it can be seen that the composite copper foil prepared by the preparation method of the present invention has good adhesion between the PP base film and the conductive film layer and the copper film layer, and has excellent conductive properties.

[0071] From the comparison of the performance results of Example 1 and Comparative Example 1, it can be seen that when the acrylic resin is replaced by the polyurethane resin, the adhesion and conductivity are both reduced, indicating that when the acrylic resin is used, the composite copper foil of the present invention has more excellent performance.

[0072] From the comparison of the performance results of Example 1 and Comparative Example 2, it can be seen that when the PP base film is not punched, its adhesion and conductivity are reduced. This may be because, when the PP base film after punching is copper-plated, a copper film layer can be formed in the through hole, and the copper film layer in the through hole is connected to the copper film layers located on the upper and lower surfaces of the PP base film, further improving the connection between the copper film layer and the PP base film. At the same time, the copper film layers located on the upper and lower surfaces of the PP base film can transmit current to each other. Compared with the PP base film without punching, the two copper layers can conduct electricity at the same time, which improves the conductive effect of the composite copper foil. Therefore, the PP base film after punching can improve the adhesion and conductivity effects at the same time.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite copper foil, characterized in that: include: (1) performing corona treatment on the upper and lower surfaces of the PP base film to obtain a surface-treated PP base film; (2) punching holes in a direction perpendicular to the upper and lower surfaces of the surface-treated PP base film to form a plurality of through holes to obtain a porous PP base film; (3) coating a conductive paste on the upper and lower surfaces of the porous PP base film to form a conductive film layer, wherein the conductive paste comprises an acrylic resin and a conductive agent; (4) Electroplating copper on the upper and lower surfaces of the conductive film layer to form a copper film layer and simultaneously fill the through hole.

2. The method for preparing the composite copper foil according to claim 1, characterized in that: The acrylic resin is a solvent-based acrylic resin with a solid content of 10-30%.

3. The method for preparing the composite copper foil according to claim 1, characterized in that: The conductive agent is selected from at least one of graphite, graphene, carbon nanotubes, nano silver wires and metal particles, and the mass percentage of the conductive agent in the conductive paste is 3-10%.

4. The method for preparing the composite copper foil according to claim 1, characterized in that: The sheet resistance of the conductive film layer is 0.5-20Ω.

5. The method for preparing the composite copper foil according to claim 1, characterized in that: The aperture of the through hole is 0.2-0.5 μm, and the distance between two adjacent through holes is 2-5 mm.

6. The method for preparing the composite copper foil according to claim 1, characterized in that: The thickness of the PP base film is 2 to 100 μm.

7. The method for preparing the composite copper foil according to claim 1, characterized in that: The thickness of the conductive film layer is 0.5-5 μm.

8. The method for preparing the composite copper foil according to claim 1, characterized in that: The thickness of the copper film layer is 0.5-2 μm.

9. The method for preparing the composite copper foil according to claim 1, characterized in that: The plating solution used for the copper electroplating includes 80-150 g / L of copper sulfate, 50-120 g / L of sulfuric acid and 0.01-2 g / L of additives, the copper plating temperature is 20-35° C., the copper plating current density is 2-10 ASD, and the copper plating time is 1-20 min.

10. A composite copper foil, characterized in that: The preparation method is described in any one of claims 1 to 9.

Citation Information

Cited By

  • Composite copper foil PP film with low melt index and high molecular weight

    CN120439628A